Identitätsprozesse junger lesbischer und bi Frauen Tanz zwischen Heteronormativität und lesbischem/bi Selbstbewusstsein - Kuhnert, Tobias (Young Academics: Soziale Arbeit, 2023)
In this grounded theory research study, the author examines identity processes among young lesbian/bi women in German-speaking Switzerland by focusing on the conditions of and contributing factors to these processes as well as the actions of young lesbian/bi women. Nine narrative interviews with 15 to 25-year-old lesbian/bi women provide the data basis. The identity processes are depicted in a model and appear in particular as the impact of heteronormativity and the women's struggle with it, as well as a growing lesbian/bi self-awareness as a result of various factors and strategies. The author discusses the results theoretically and in relation to the current state of research. Finally, he outlines their implications for social work practice.